Strategic Brand Concept-Image Management - Park, C. Whan; Jaworski, Bernard J.; MacInnis, Deborah J. (Journal of Marketing, 1986)
Conveying a brand image to a target market is a fundamental marketing activity. The authors present a normative framework, termed brand concept management (BCM), for selecting, implementing, and controlling a brand image over time. The framework consists of a sequential process of selecting, introducing, elaborating, and fortifying a brand concept. The concept guides positioning strategies, and hence the brand image, at each of these stages. The method for maintaining this concept-image linkage depends on whether the brand concept is functional, symbolic, or experiential. Maintaining this linkage should significantly enhance the brand's market performance.